Divergent effects of forest edges on host distribution and seed disperser activity influence mistletoe distribution and recruitment. (21st September 2015) - Magrach, Ainhoa; Rodríguez‐Pérez, Javier; Piazzon, Martín; Santamaría, Luis; Heard, Matthew
Summary Species interactions define functional diversity and community stability across ecosystems, and depend on the spatial distribution, the habitat requirements and the sensitivity to disturbances of all interacting partners. Hence, assessing the effects of such anthropogenic disturbances on multi‐species interactions may be essential to improve adaptation and mitigation measures for biodiversity conservation. We determined the importance of edge effects on the interaction and distribution of three keystone species in South American temperate rain forests: the hemiparasitic mistletoe Tristerix corymbosus, its main host (the liana Campsidium valdivianum) and its only seed disperser (the marsupial Dromiciops gliroides). The discordant impacts of forest edges on host (positive) and seed disperser (negative) affected mistletoe distribution at large spatial scales, owing to the combined effects of increased dispersal limitation and decreased host availability. More importantly, marsupial abundance had contrasting effects on mistletoe abundance at small and large spatial scales – suggesting a potential trade‐off between local and long‐distance dispersal. We found the number of adult mistletoes per host increased with host size, which likely indicates that mistletoe colonization accumulated over the host's lifespan. However, the number of juveniles found per host peaked at medium‐sized hosts, increased with marsupial abundance and host availability and showed a negligible response to edges. Synthesis. The lack of spatial congruence between host and seed disperser probably explains the scarcity of mistletoes in the study area, although the discordant drivers of juvenile and adult distributions suggest that there is a trade‐off between recruitment patterns but also potential dispersal limitation at small scales. In essence, the interdependence amongst species linked by (mutualistic and antagonistic) interactions makes them more sensitive to anthropogenic disturbance, exacerbating its impact on the diversity and functioning of forest ecosystems.